An empirical analysis of Singapore’s monetary and exchange rate policies in the 1990s - MAYSAMI, R.C.; SOH, C.S. (PSL Quarterly Review, 2013)
The economy of Singapore has remained relatively unscathed from the Asian currency crisis of 1997 and 1998 which has severely crippled the markets of Hong Kong, Indonesia, and Malaysia. The Monetary Authority of Singapore, which has overseen the country's financial development since the 1960s, has maintained sound monetary policy which has saved the economy from ruin. The government, unlike those of other countries, has also regulated real estate loans and land development and has strengthened its basic services of telecommunications and transport. The present work seeks to re-examine the conflict between monetary stability and exchange rate objectives. The authors seek to find out which policy goal the Monetary Authority of Singapore has been and should be more interested in. JEL Codes: E02, E52